FUNGSI DAN TEKNIK PERMAINAN ALAT MUSIK TRADISIONAL MANDAILING UYUP-UYUP DI DESA PARGARUTAN JAE TAPANULI SELATAN - Eben Ezer Silaban (Universitas Negeri Medan, 2018)
This study aims to determine Function, Game Techniques and Organic Uyup-Uyup In PargarutanVillage Jae Tapanuli Selatan. The purpose of this research is to know the function, game techniqueand organology of mandailing uyup-uyup instrument in Pargarutan Jae Tapanuli Selatan Villagecommunity. The theory used is function, game technique and organology. The function of music isto express the taste and simultaneously as an activity of various types of human communication.Organology is the study of the structure of musical instruments based on sound sources, how toproduce sounds and system of alignment. Game technique is a way or technique of touch on amusical instrument over a particular tone according to the instructions or notation. The methodused in this research is qualitative descriptive method. The sample in this research is one artist andfive people of Pargarutan Jae Village. Data collection was done by observation, interview, anddocumentation. This research was taken in Pargarutan Jae Village, and this research was carriedout from October 2017. The function of Uyup-uyup music instrument in South Tapanuli there arethree of the first is the function of emotional disclosure is a medium for someone to express feelingsand emotional through the game of uyup-uyup instruments that use systematic way of presentingthe sound. The second is the entertainment function in which the South Tapanuli also needentertainment that is the entertainment of playing a uyup-uyup instrument at rest in the rice fields.Third is the Communication Function where when calling the opposite sex across the paddy fieldthe man repeatedly played uyup-uyup. Organic musical instrument Uyup-uyup consists of fiveparts, namely rice stalks, coconut leaves and lidi as a binder of coconut leaves. The game techniquein the uyup-uyup instrument is divided into the first three sections that are played in a sitting /standing position, the second way of blowing uyup-uyup is by way of the mouth is placed at thebase of the top of the uyup-uyup instrument, the third position of the finger finger, first startingfrom the left hand with the beginning of the index finger and the second hole of the middle fingerand then on the right hand begins with the index finger and the hole of both middle fingers.